2019
DOI: 10.1038/s41598-019-54985-3
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Selenate Ameliorates Cardiac Injury Developed from High-Fat Diet in Mice through Regulation of Autophagy Activity

Abstract: Obesity is often accompanied by dyslipidemia, high blood glucose, hypertension, atherosclerosis, and myocardial dysfunction. Selenate is a vital antioxidant in the cardiovascular system. The beneficial effects of selenate on obesity-associated cardiac dysfunction and potential molecular mechanism were identified in both H9C2 cells and C57BL/6J mice hearts. The cardiac histological preformation in C57BL/6J mice were evaluated by cross-sectional area (CSA) of cardiomyocytes and percent area of fibrosis in the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The molecular mechanisms of autophagy regulation remain unclear, an in-depth study of mTOR-4EBP1 pathway might thus contribute to provide an exciting therapeutic strategy for DCM [24][25][26]. Our data indicated that rapamycin down-regulated the mTOR-4EBP1 signaling pathway in DCM mice.…”
Section: Discussionmentioning
confidence: 66%
“…The molecular mechanisms of autophagy regulation remain unclear, an in-depth study of mTOR-4EBP1 pathway might thus contribute to provide an exciting therapeutic strategy for DCM [24][25][26]. Our data indicated that rapamycin down-regulated the mTOR-4EBP1 signaling pathway in DCM mice.…”
Section: Discussionmentioning
confidence: 66%
“…This suggests that the overproportional lipid accumulation is no direct effect of spermidine but is rather based on an interaction between the cellular disturbances induced by HFD and spermidine. For example, cell culture and mouse experiments indicate that high lipid burden leads to increased autophagosome generation but less autophagosome degradation (Zhang et al 2019 ). Additional interference with the dysregulated autophagic machinery by exogenous spermidine might therefore increase the imbalance and have adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms of autophagy regulation remain unclear, an in-depth study of mTOR-4EBP1 pathway might thus contribute to provide an exciting therapeutic strategy for DCM [24][25][26].…”
Section: Discussionmentioning
confidence: 99%